Chinese Foreign policy towards Africa - Zhang, Wenhua; Garlick, Jeremy; Qin, Fangxing; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
This article mainly introduces the four main foreign policies China adopts towards Africa and explains explicitly that China’s foreign policy focuses on different African countries using different instruments through case studies in Nigeria and Ethiopia. It can be seen that the implementation of China's foreign policy in Africa is full of controversy. From the Chinese perspective, more consideration is to establish a win-win relationship with Africa, but the Western media are more skeptical of China's aid to Africa plan whose voice of China feels that it is an extension of Chinese hegemonism. Implementing such a controversial foreign policy, China should continuously adjust the way of international aid to reduce the trend of hegemonism, and African countries should combine their own actual conditions to form a unified and clear diplomatic strategy to solve the problem of China and the West. The West should also face China’s aid to Africa more objectively and fairly, so as to promote the harmonious development of the international community and achieve a real win-win result.
Vedoucí práce: Jeremy Alan Garlick
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses